Different VDR, VDBP genotypes and vitamin D levels may effect obstructive sleep apnea syndrome - Kirac, Deniz; Yagcioglu Yassa, Ozge; Gezmis, Hazal; Mayda Domac, Saime Fusun; Altunok, Elif Cigdem; Genc, Ece (Cellular and Molecular Biology, 2019)
Obstructive sleep apnea syndrome (OSAS) is a highly prevalent disorder which results in markedly reduced (hypopnea) or absent (apnea) airflow at the nose/mouth. Since vitamin D deficiency has found in an association with some disorders it is thought to be related with OSAS progression. The aim of this study is to investigate the association between VDR, VDBP mutations, vitamin D level and some environmental risk factors with OSAS. Fifty individuals who were diagnosed as OSAS were selected as patients, 50 healthy volunteers without any disease were selected as controls. FokI (rs2228570) and BsmI (rs1544410) mutations in VDR; rs4588 and rs7041 mutations in VDBP were investigated with quantitative real-time polymerase chain reaction (qPCR). Other risk factors were also investigated. Results were evaluated statistically. Statistically significant differences were observed according to the baseline characteristics between the groups, When groups were compared with each other, CA genotype in rs4588, CC genotype in rs2228570 and AA genotype in rs1544410 mutations were found statistically significant in patients whereas TC genotype in rs2228570 and GA genotype in rs1544410 mutations were found statistically significant in controls. When the relation between risk factors and genotypes were investigated, statistically significant associations were detected for body mass index (BMI), waist circumference, Apnea–Hypopnea Index (AHI), excessive daytime sleepiness (EDS), vitamin D and triglyceride levels. VDR and VDBP mutations were found highly related with OSAS. Possible tracking of these mutations and risk factors may help to understand the metabolism as well as the progression of the disease.